Yield, chemical composition, and bioactivity of essential oils from 12 species of Eucalyptus on Aedes aegypti larvae - Lucia, Alejandro (2008)
The insecticidal activity of essential oils from 12 species of Eucalyptus (Myrtaceae) was evaluated on larvae of Aedes aegypti (L.) (Diptera: Culicidae), the most important vector of dengue and yellow fever in the Americas. Oils were obtained by hydrodistillation and their chemical composition was determined by gas chromatography coupled to mass spectrometry; yields ranged from 0.2 to 2.5%. Essential oils were mainly composed of 1,8-cineole, α-pinene, α-phellandrene, β-phellandrene, γ-terpinene, 4-terpineol, α-terpineol, p-cymene, and spathulenol. Larvicidal effects were tested on susceptible third or fourth stage Ae. aegypti larvae, determining median lethal concentration (LC50) and median effective concentration (EC 50). Essential oils from Eucalyptus dunnii (Maiden), Eucalyptus gunnii (Hook), Eucalyptus tereticornis (Smith), Eucalyptus camaldulensis (Dehn), and Eucalyptus saligna (Smith) showed the best larvicidal activities with LC50 values of 25.2, 21.1, 22.1, 26.8, and 22.2, respectively. No significant differences were observed between LC50 and EC 50 values of the same oil. Regression analysis revealed a significant relationship between total essential oil yields and 1,8-cineole concentration. Significant relationships were also revealed between larval mortality and the concentration of 1,8-cineole and p-cymene. This indicated that Eucalyptus species with high oil yields have higher 1,8-cineole concentrations and lower p-cymene concentrations and have less effect on Ae. aegypti. Our results suggest the potential of controlled crossing methods to obtain Eucalyptus trees with chemical profiles having enhanced activity against this mosquito.